A Multi-Site Auto-Ethnographical Investigation Of Three African-Centered Schools - Tengella, Renee Frances (My University, 2012)
This dissertation was a multi-site auto-ethnographic case study that used personal recollections, researcher experiences, interviews, and survey data to describe the curriculum, pedagogy, and learning environment of three African-centered schools located in Baltimore, MD, Trenton, NJ, and Washington, DC. The initial aim of the study was to describe the African-centered school and determine if these schools represented examples of Nguzo Saba principles (African-centered cultural values). Next, the researcher sought to determine if the students had adopted these principles as measured on the Optimal Extended Self Esteem Scale (OESES). The OESES data collected from the students and the adult perceptions from interviews revealed information about the African-centered schools and the Nguzo Saba principles (African-centered cultural values) adopted by these students. Observations, interviews, and surveys were conducted between January 2008 and December 2009. The data collected revealed a common theme of the Nguzo Saba in the curriculum, pedagogy, and learning environment. This study asserted that African-centered schools and the comprehensive application of Nguzo Saba principles would generate positive responses on the OESE survey. Students' responses on the OESES were representative of their African-centered cultural values (Nguzo Saba values). Parent, teacher, and administrator responses supported a view of students as being family and community centered. The results of the student survey combined with interviews of administrators, teachers, and parents perceptions revealed that African-centered cultural values based on the Nguzo Saba principles of Umoja (unity), Kujichagulia (self-determination), Nia (purpose), Kuumba (creativity), and Imani (faith) were transmitted to students. The results of this study were expressed in a personal narrative that comprises Chapters IV through V. Chapters I through III present a traditional dissertation model that includes the introduction, review of literature, and research methodology. Chapter V offers recommendations, a discussion of the findings and concluding remarks.
Keywords: Education; Curriculum planning; Education--Curricula; African American studies; Education